Gerakan Cegah Stunting Edukasi Gizi Seimbang Melalui Pengenalan Makanan Sehat untuk Ibu dan Balita di Desa Margosari Kabupaten Kendal - Athallah, Ferdy Bagas; Hadmah, Afrida Ghautsiyah; Soleha, Vaella Silfa; Febrianti, Nurul (Jurnal Bina Desa, 2025)
Stunting is a very crucial global problem, influenced by socio-economic factors such as high poverty, high rates of early marriage, and low public knowledge. The purpose of this community service activity is to increase public awareness and knowledge about the importance of balanced nutrition and practical steps to prevent stunting. The community service method applied is socialization and training targeting mothers who have toddlers in Margosari Village. The results of the community service show that mothers can understand the urgency of providing food with balanced nutrition and maintaining health. In this community service, mothers can also make a menu of tempeh nuggets, potato cakes, and cream shop from corn. These menus are rich in protein that can support the growth and development of toddlers during their growth period. Mothers can also get used to serving varied and economical menus from vegetables in their respective gardens or yards.